2009
DOI: 10.22452/fiqh.vol6no1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Code of Muslim Family Law and Law of Inheritance (1941) As Applicable in the Provincial Courts of Southern Four Border Provincess of Thailand: Issues and Prospects

Abstract: of the Code and the course of future direction by exploring the available alternative according to Thai Constitution to the continued pursuit of reforming several articles in the code towards the Codification of Islamic Family Law in the Four Southern Border Provinces of Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The problem faced is related to the law, so the solution comes from some of Shafi'i's fictional books carried out by Judge Datoh and has binding power. Some of them are Fathul Mu'in, Mughni al-Muhtaj, Al-Bajuri 'Ala al-Syamsyuri, Ghayat al-Maqsud, Halal Musykilat, and Syarh al-'Arabiyyah (Dorloh, 2009).…”
Section: Application Of Sharia Law In Muslim Minority Territoriesmentioning
confidence: 99%
“…The problem faced is related to the law, so the solution comes from some of Shafi'i's fictional books carried out by Judge Datoh and has binding power. Some of them are Fathul Mu'in, Mughni al-Muhtaj, Al-Bajuri 'Ala al-Syamsyuri, Ghayat al-Maqsud, Halal Musykilat, and Syarh al-'Arabiyyah (Dorloh, 2009).…”
Section: Application Of Sharia Law In Muslim Minority Territoriesmentioning
confidence: 99%
“…In these countries, the zakah practice relies on uniform laws and statutory provisions that regulate the administration of zakah at the national level. In contrast, Dorloh, et al (2020) identified the problem of centralized zakah management practice in Thailand where Muslims are a minority, and advocated for localization of zakah distribution as a conceivable solution to address the problem thereby satisfying the needs of the actual zakah stakeholders (zakah payers/recipients). Ummulkhayr et.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a recent fatwa issued by ACJU read "zakah is not levied on fruits except grapes and dates, and it is not levied on coconut and vegetables" (ACJU/FTW/2017/ 2015). Yet, the experience from notable zakah institutions operating in some other Muslim minority countries such as Thailand, India, and Singapore suggests that the minority Muslims can endeavor via institutional setup to preserve zakah obligation and achieve some of its wider objectives including enhancing spirituality, establishing social justice, reducing poverty, enhancing social welfare, ensuring stable economic growth and inter and intra-community relationships (Dorloh, et al, 2020;Rahmani, 2019).…”
Section: Introductionmentioning
confidence: 99%